Ice Breakup on the Chena River-1975 and 1976 - McFadden, Terry T; Collins, Charles M (1977)
The breakup of the Chena River was observed and documented during the spring of 1975 and 1976. This study attempted to determine the potential for damage to the proposed Chena River flood control dam from ice and debris during breakup. Results of this study were compared to those of a 1974 companion study. In 1975, ice thickness were determined to be 15% thinner than in 1974 and ice volume was 33% smaller. No major ice floes were observed in 1975 and no significant flooding occurred, although the approaches to a bridge at the damsite were eroded by debris and high water immediately after breakup. The 1976 breakup was milder than that of 1975. Minor flooding in the lower river was caused by jamming of a few large ice pieces, but no property damage resulted.